EFEKTIVITAS MODEL PEMBELAJARAN LEARNING CYCLE 5E TERHADAP MISKONSEPSI SISWA KELAS IV PADA MATERI GAYA - Siti Quraini Nurfadilah; Ahmad Mulyadiprana; Agnestasia Ramadhani Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the effectiveness of the Learning Cycle 5E model in reducing misconceptions among fourth-grade elementary students on the topic of force. The research employed a quasi-experimental method with a nonequivalent control group design. The participants consisted of 66 students: 33 students from SDN 1 Giriawas as the control group and 33 students from SDN 2 Giriawas as the experimental group. The research instrument was a multiple-choice test with the Certainty of Response Index (CRI) to identify students’ misconceptions. The results indicated that before the treatment, most students experienced misconceptions regarding force concepts. After applying the Learning Cycle 5E model, the number of misconceptions in the experimental class significantly decreased compared to the control class. The N-Gain test showed that the conceptual understanding improvement in the experimental group was in the medium category, while the control group was in the low category. Moreover, the independent sample t-test confirmed a significant difference between the two groups. Therefore, the Learning Cycle 5E model is proven effective in reducing misconceptions and can be recommended as an alternative instructional strategy for science learning in elementary schools.